2015
DOI: 10.1111/bjh.13528
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma and non‐melanoma skin cancers in hairy cell leukaemia: a Surveillance, Epidemiology and End Results population analysis and the 30‐year experience at Memorial Sloan Kettering Cancer Center

Abstract: Few studies have examined melanoma and non-melanoma skin cancer (NMSC) incidence rates after a diagnosis of hairy cell leukaemia (HCL). We assessed 267 HCL patients treated at Memorial Sloan Kettering Cancer Center (MSKCC) and Surveillance, Epidemiology and End Results (SEER) data for melanoma and NMSC incidence rates after HCL. Incidence data from MSKCC patients demonstrated a 10-year combined melanoma and NMSC skin cancer rate of 11.3%, melanoma 4.4% and NMSC 6.9%. Molecular analysis of skin cancers from MSK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In other studies, HCL patients did not have a higher risk of developing a second cancer (Table 5) [21][22][23][24]40,43,50 . Some studies found an excess of risk only for certain cancers (Table 5) [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, HCL patients did not have a higher risk of developing a second cancer (Table 5) [21][22][23][24]40,43,50 . Some studies found an excess of risk only for certain cancers (Table 5) [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of patient age has not been assessed as a factor for predicting secondary cancers in this disease. A study from our group showed that HCL treated after the introduction of cladribine did not measurably increase the incidence of melanoma beyond the expected population rate (Watts et al , ); however, patients were not stratified by age at diagnosis in this report, which may be relevant given the differences in lifestyle and cumulative ultraviolet exposure in younger individuals (Watts et al , ). The issue of skin malignancy was of particular concern in the phase 2 study of vemurafenib, which resulted in investigators limiting drug exposure to 6 months because of concerns that BRAF inhibition could, paradoxically, increase the growth of RAS ‐mutated cancers (Su et al , ).…”
mentioning
confidence: 80%
“…A recent study by Watts et al reported no statistically significant increased risk of melanoma in HCL patients, compared to the general population [88]. Vemurafenib can further increase the incidence of secondary skin cancer events.…”
Section: Braf Inhibitorsmentioning
confidence: 91%